(untitled) (Journal of Health, Population and Nutrition, 2009)
A cross-sectional study was conducted to investigate the potential factors of food-hygiene practices of mothers on the prevalence of diarrhoea among their children. Mothers who had children aged 6 months-5 years were recruited in a hamlet in Viet Nam. The food-hygiene practices included hand-washing, method of washing utensils, separation of utensils for raw and cooked food, and the location where foods were prepared for cooking. A face-to-face interview was conducted, and data on 206 mothers were analyzed. The risk of diarrhoea was significantly higher among children whose mothers prepared food for cooking somewhere other than the table (typically on the ground) compared to children whose mothers prepared food on the table (adjusted odds ratio=2.85, 95% confidence interval 1.11-7.28). The results indicate that food-hygiene practices of mothers, such as avoiding preparing food for cooking on the ground, has a potential impact in preventing diarrhoea among children in Viet Nam. J Health Popul Nutr 2009 Oct; 27(5):602-611